(3OjhGf HgQGe TGgs - (3HgQGe TGg Hf aQhN TGg Hf TGgfTGg Hf CjhH Hf TGOj,Gdedc GdCeLO GdeXaQ , J (B628 (3g` s
(3ChdgG (B:s
(3dehdGfG GdSdWGf GdCLd eG fXeg aj GdfSjH hGdJZRd hGdMeGSI aj eOI ChdgG TgQ QeVGf GdoeYXe s
(3BNQgG (B:s
(3TYQ dg faKGJ GdSQ NGdUI ef Ohf TYQ CfGS bd eG SMQG s
(3fSNI KGfjIs
(3hHBNQgG JedjcGJs
(3haj hSWgG hQbI HgG bQGAGJ hoeWGdYGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs